2007
DOI: 10.1152/ajplung.00030.2006
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin but not ciprofloxacin or azithromycin selectively inhibits IL-8, IL-6, ERK1/2, JNK, and NF-κB activation in a cystic fibrosis epithelial cell line

Abstract: Cystic fibrosis (CF) is associated with severe neutrophilic airway inflammation. We showed that moxifloxacin (MXF) inhibits IL-8 and MAPK activation in monocytic and respiratory epithelial cells. Azithromycin (AZM) and ciprofloxacin (CIP) are used clinically in CF. Thus we now examined effects of MXF, CIP, and AZM directly on CF cells. IB3, a CF bronchial cell line, and corrected C38 cells were treated with TNF-α, IL-1β, or LPS with or without 5–50 μg/ml MXF, CIP, or AZM. IL-6 and IL-8 secretion (ELISA), MAPKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 49 publications
8
60
0
1
Order By: Relevance
“…7A and data not shown) or HIF-1␣ protein levels (Fig. 7B) in IB3-1 cells, which is supported by the observations made in a previous study (44). Moreover, PAO1 LPS and serotype 10 LPS showed distinct profiles (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…7A and data not shown) or HIF-1␣ protein levels (Fig. 7B) in IB3-1 cells, which is supported by the observations made in a previous study (44). Moreover, PAO1 LPS and serotype 10 LPS showed distinct profiles (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…Certain fluoroquinolone derivatives have been reported to selectively inhibit PI3Kg [50]; however, lomefloxacin appears to have broader effects on a number of proinflammatory signalling pathways. The findings reported here do, however, provide a mechanistic basis for the independent, empirical observation of the anti-inflammatory therapeutic benefit of moxifloxacin in a TRAPS patient [36], and concurs with other reports of inhibitory effects of moxifloxacin on MAP-kinases and NFkB [47][48][49]. However, it cannot be excluded that the beneficial effects of moxifloxacin in this patient were due to its anti-microbial activity against infections that might otherwise have triggered TRAPS-associated inflammation; furthermore, moxifloxacin and ciprofloxacin were not beneficial in three other TRAPS patients with the C33Y-TNFR1 mutation [36].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, with regard to the effects of fluoroquinolones on pro-inflammatory signaling intermediates, it has been reported that norfloxacin and gemifloxacin reduce NFkB expression and activation [43][44][45], and that garenoxacin inhibits Erk1/2 phosphorylation [46]. Moxifloxacin also inhibits Erk1/2, JNK and NFkB [47][48][49]. Certain derivatives of fluoroquinolones have been reported selectively to inhibit PI3Kg [50].…”
Section: Discussionmentioning
confidence: 99%
“…anism of NF-B inhibition by AZM is unknown but there are conflicting reports demonstrating the IB kinase-dependent and independent mechanisms for inhibition of NF-B activation by macrolide antibiotics (24,29,30). Moreover, our own data showed that the TNF-␣-induced IB-␣ degradation (which occurs mainly via IB kinase beta or IKK2-dependent mechanism) is blocked by AZM in TA cells, thereby suggesting that the AZM inhibited NF-B activation by IB-␣ degradation.…”
mentioning
confidence: 99%